Bad Debt Restructuring Policy for Micro, Small, and Medium Enterprises in Yogyakarta: An Evaluative Study from the Maṣlaḥah Perspective - Halim, Abdul; Wahyuni, Sri; Abidin, Ratnasari Fajariya (UIN Sunan Kalijaga, 2025)
The Covid-19 pandemic has been declared over in recent years; however, economic activity—particularly among Micro, Small, and Medium Enterprises (MSMEs)—has yet to stabilize, leading to challenges for some enterprises in fulfilling their credit obligations. Utilizing the maṣlaḥah (beneficial interest) framework, this study aims to evaluate the bad credit restructuring policy for MSME entrepreneurs in Yogyakarta. This research employs a normative juridical approach, incorporating observation, interviews, and document analysis to examine the implementation of Financial Services Authority Regulations No. 17/POJK.03/2020, which addresses bad credit restructuring for MSME entrepreneurs. The findings reveal that the restructuring and relaxation of bad credit measures following the Covid-19 pandemic function as policies intended to facilitate compromise between creditors and debtors amid ongoing economic instability. The study underscores that this policy yields significant benefits for all stakeholders involved and asserts that these benefits align with the concept of maṣlaḥah mu’tabarah (significant beneficial interest), indicating their endorsement and obligation within the Islamic legal framework.